The diurnal cycle of sea‐surface temperature and estimation of the heat budget of the Mediterranean Sea. Issue 11 (28th November 2016) - Marullo, S.; Minnett, P. J.; Santoleri, R.; Tonani, M.
ABSTRACT: The diurnal cycle in sea‐surface temperature (SST) is reconstructed for the year 2013 by combining numerical model analyses and satellite measurements using Optimal Interpolation (OI). The method is applied to derive hourly Mediterranean SST fields using Spinning Enhanced Visible and Infrared Imager (SEVIRI) data and Mediterranean Forecasting System analyses (Copernicus Marine Environment Monitoring Service ‐ Analysis and Forecast product). The evaluation of the Diurnal OI SST (DOISST) values against drifter measurements results in a mean bias of −0.1°C and a RMS of 0.4°C. The DOISST fields reproduce well the diurnal cycle in SST including extreme Diurnal Warming events as measured by drifting buoys. We evaluate the impact of resolving the SST diurnal cycle, including extreme events, on estimates of the heat budget of the Mediterranean Sea over an entire annual cycle. It results in the mean annual difference in the heat loss derived using SSTs with and without diurnal variations of 4 Wm −2 with a peak of 9 Wm −2 in July. This value is comparable to several other sources of uncertainty in the calculation of the heat and water budgets of the Mediterranean Sea. The results are an important step toward reducing uncertainties in the "Mediterranean Sea Heat Budget Closure Problem". Key Points: Diurnal SST signals in drifting buoy data in the Mediterranean Sea are replicated in SEVIRI data Neglecting diurnal SST effects leads to errors in estimates of air‐sea heat and moisture fluxes Consequences of such errors on the Mediterranean Sea heat and mass balances are not negligible